E-Satisfaction dalam Memediasi Pengaruh Habit dan Personalization terhadap Continuance Intention pada Konsumen Muslim Pengguna Spotify di Jawa Tengah - Fitriyana, Fitriyana; Fitriyani, Fitriyani; Maharany, Indah Dewi (BISNIS, 2026)
The subscription-based music streaming industry faces the challenge of high churn, while Muslim consumers in Central Java have distinct characteristics and content preferences that may influence their habits and personalization when using Spotify. This study aims to examine the influence of habits and personalization on continuance intention through e-satisfaction as a mediating variable. This study employs a quantitative approach with an explanatory and correlational design. A sample of 100 Muslim Spotify users in Central Java was selected using purposive sampling. Data were collected via a closed-ended questionnaire using a 1–5 Likert scale and analyzed using Partial Least Squares-based Structural Equation Modelling (SEM-PLS) with SmartPLS 4.0. The results show that habit has a positive and significant effect on continuance intention (0.300) and e-satisfaction (0.447); personalization has a positive and significant effect on e-satisfaction (0.470) but has no direct effect on continuance intention (0.082; p=0.453); e-satisfaction has a positive and significant effect on continuance intention (0.581) and mediates the effects of habit (0.260) and personalization (0.273) on continuance intention. The model shows a good goodness of fit with an SRMR of 0.054 and an NFI of 0.813. In conclusion, e-satisfaction plays a central role as a mediator in shaping the continuance intention of Muslim consumers who use Spotify in Central Java, so that strategies to strengthen habit and personalization should be directed toward enhancing user satisfaction while ensuring content aligns with Islamic values.